The Effectiveness of Digital Political Communication in Increasing Generation Z Political Participation in Indonesia - Salim, Sarah Amalina (Darul Yasin Al Sys, 2025)
This study investigates the effectiveness of digital political communication in enhancing the political participation of Generation Z in Indonesia. The research is grounded in the context of a digitally native generation that relies heavily on social media platforms, such as Instagram, TikTok, X/Twitter, and YouTube for accessing information, shaping opinions, and engaging with political discourse. Given Generation Z’s growing electoral significance, understanding the strategic role of digital communication in fostering their political engagement is increasingly critical. Employing a quantitative approach, data were collected through an online questionnaire distributed to 380 respondents aged 17–27 years, selected via purposive sampling. Criteria included active use of social media for political information and recent interaction with digital political content within the past six months. Data analysis involved descriptive statistics and multiple linear regression to assess the relationship between the effectiveness of digital political communication and levels of political participation. Findings reveal a significant positive impact, particularly in raising political awareness, stimulating online political discussions, and increasing intentions to vote. Key drivers of engagement include source credibility, message clarity, and the appeal of visual-based media. However, the study also identifies challenges such as misinformation, content fatigue, and limited digital literacy. The study concludes that digital political communication can effectively increase political participation among Generation Z when implemented through creative, transparent, and educational strategies. These insights offer practical implications for political actors, election bodies, and civil society organizations aiming to design inclusive and sustainable digital engagement campaigns.